Urgensi Pembentukan Peraturan Perundang-Undangan Teknologi Berbasis Artificial Intelligence - Mufti, M. Wildan; Ikhsan, M. Hiroshi; Sani, Rafif; Fauzan, M. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of Artificial Intelligence (AI) in Indonesia presents both significant opportunities and challenges that require specific regulations. Although the Information and Electronic Transactions Law (ITE Law) regulates digital aspects, this regulation is considered inadequate to handle the complexity of AI. Issues of privacy and data misuse underscore the importance of stringent regulations. Through the Social Engineering approach by Roscoe Pound, law as a tool of social control can ensure responsible AI use. This research employs a normative juridical method with statutory and conceptual approaches to analyze the urgency and obstacles of forming AI regulations. Collaboration between the government, private sector, and society is necessary to create regulations that protect individual interests and promote innovation. With effective regulations, Indonesia can optimize the potential of AI safely and sustainably, ensuring justice and inclusivity in accessing this technology.